French EEZs in the Pacific in the context of ocean change - Joanna Siekiera (Lex Portus, 2020)
France is present in the Pacific region via its overseas collectivities being French Polynesia, New Caledonia, and Wallis & Futuna. This geostrategic region is also called the Blue Pacific bearing in mind its enormous maritime areas in comparison to the land. 93% of French Exclusive Economic Zones (EEZs) are located in the Indian and Pacific Oceans. The area itself is home to 1.5 million French people, as well as 8,000 soldiers stationed in the region. It has also become a strategical and global economy’s centre of gravity, which had shifted from the Atlantic to the Pacific. The maritime trade routes linking Europe and the Persian Gulf, via the Indian Ocean and South-East Asia, to the Pacific Ocean, have become very important. The Pacific’s growing share of world trade and investment means that it is at the forefront of globalization. Therefore further research on this geopolitical region seems to be crucial and requires deeper analysis, also when it comes to the discipline of public international law and international relation. Ocean change is now the biggest threat facing the Pacific islands because of the loss of territory, and thus sovereignty of the submerged states. Another factor is the downsizing of EEZs and possible and already existing political tensions between France and its collectivities and the rest of the countries in the region.